2011
DOI: 10.1016/j.clinph.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Lempel–Ziv complexity in schizophrenia: A MEG study

Abstract: SchizophreniaLempel-Ziv complexity Magnetoencephalography Neurodevelopmental Neurodegenerative• Schizophrenic patients show higher complexity values as compared to controls.• Schizophrenic patients showed a tendency to reduced complexity values as a function of age while controls showed the opposite tendency.• The tendency observed in schizophrenic patients parallels the tendency observed in Alzheimer disease patients. ABSTRACTObjective: The neurodevelopmental-neurodegenerative debate is a basic issue in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 52 publications
8
73
0
4
Order By: Relevance
“…Measures of complexity (including those developed in our research) have provided a useful tool for differentiating people of different age groups (McIntosh et al, 2008; McIntosh et al, 2014; Smith et al, 2014; Takahashi et al, 2009; Vakorin et al, 2011; Yang et al, 2013a) and with different clinical disorders including Alzheimer’s disease (Escudero et al, 2006; Mizuno et al, 2010; Yang et al, 2013b), autism (Bosl et al, 2011; Catarino et al, 2011; Ghanbari et al, 2015), attention deficit hyperactivity disorder (Gomez et al, 2013; Sokunbi et al, 2013), depression (Mendez et al, 2012; Niemiec and Lithgow, 2005; Saletu et al, 2010), SZ (Fernandez et al, 2011; Sokunbi et al, 2014; Takahashi et al, 2010; Yang et al, 2015), and traumatic brain injury (Lu et al, 2012; Raja Beharelle et al, 2012). Of note, the interpretation of complexity is often by the simple up vs. down approach in a single time scale along the continuum of regularity toward randomness, leading to the confusing conclusion that randomness is complex.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Measures of complexity (including those developed in our research) have provided a useful tool for differentiating people of different age groups (McIntosh et al, 2008; McIntosh et al, 2014; Smith et al, 2014; Takahashi et al, 2009; Vakorin et al, 2011; Yang et al, 2013a) and with different clinical disorders including Alzheimer’s disease (Escudero et al, 2006; Mizuno et al, 2010; Yang et al, 2013b), autism (Bosl et al, 2011; Catarino et al, 2011; Ghanbari et al, 2015), attention deficit hyperactivity disorder (Gomez et al, 2013; Sokunbi et al, 2013), depression (Mendez et al, 2012; Niemiec and Lithgow, 2005; Saletu et al, 2010), SZ (Fernandez et al, 2011; Sokunbi et al, 2014; Takahashi et al, 2010; Yang et al, 2015), and traumatic brain injury (Lu et al, 2012; Raja Beharelle et al, 2012). Of note, the interpretation of complexity is often by the simple up vs. down approach in a single time scale along the continuum of regularity toward randomness, leading to the confusing conclusion that randomness is complex.…”
Section: Discussionmentioning
confidence: 88%
“…Brain complexity in SZ has been examined using electroencephalography (Keshavan et al, 2004; Takahashi et al, 2010), magnetoencephalography (Fernandez et al, 2011), and gyral folding using structural MRI (Narr et al, 2004). A valuable approach to investigating the complexity of brain activity in SZ is resting-state fMRI.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that schizophrenics and patients with depressive disorders exhibit a high LZC (Li et al, 2008). The level of complexity changes with patients' age (Fernández et al, 2011(Fernández et al, , 2012. Alzheimer patients show an abnormally low LZC (e.g., Hornero et al, 2009;Dauwels et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, EEG dimensional complexity in schizophrenia was lower than that in healthy controls [9]. In EEG studies, abnormal brain activity in schizophrenia patients can be detected using nonlinear analysis algorithms such as dimensional complexity [10], correlation dimension (D2) [11], Lempel_Ziv complexity (LZC) [12], approximate entropy (ApEn) [13], mutual information (MI) [14], and fractal dimension (FD) [15]. Among these algorithms, FD is applicable to nonlinear analysis of non-stationary and transient time series data like EEG signals [16], but FD has several limitations in stationary, noise-free, and long time series data.…”
Section: Introductionmentioning
confidence: 99%